Pengembangan E-Comic Basak Terhadap Berpikir Kritis Dan Hasil Belajar Siswa - Hafidz Baharuddin Yusuf; Liyana Sunanto (PT. AHLAL PUBLISHER NUSANTARA, 2025)
This study aims to analyze the impact of developing the BASAK e-comic learning media on improving students’ critical thinking skills and learning outcomes through a Systematic Literature Review (SLR) approach. The review involved 30 scientific articles published between 2020 and 2025, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) guidelines. The results indicate that the use of e-comics consistently produces positive effects on the enhancement of students’ critical thinking and learning performance, particularly at the elementary and secondary education levels. E-comics effectively improve students’ ability to analyze, evaluate, and draw conclusions through engaging narratives and interactive visuals. In addition, students’ learning outcomes increased by an average of 15–30% after using e-comics in the learning process. These findings are supported by Mayer’s multimedia learning theory, which suggests that the combination of text and images facilitates dual-channel processing, thereby strengthening conceptual understanding and memory retention. However, most of the reviewed studies were limited by quasi-experimental designs, short intervention durations, and the use of non-standardized instruments for measuring critical thinking. Therefore, further research using randomized experimental designs and larger sample sizes is recommended to examine long-term effectiveness. Overall, the SLR findings confirm that the BASAK e-comic represents an effective digital learning innovation for enhancing critical thinking and learning outcomes, aligning with the demands of 21st-century education. Keywords: BASAK e-comic, critical thinking, learning outcomes, digital learning, SLR Abstrak Penelitian ini bertujuan untuk menganalisis pengaruh pengembangan media e-comic BASAK terhadap peningkatan kemampuan berpikir kritis dan hasil belajar siswa melalui pendekatan Systematic Literature Review (SLR). Kajian dilakukan terhadap 30 artikel ilmiah terbitan tahun 2020–2025 dengan menggunakan panduan Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020). Hasil penelitian menunjukkan bahwa penggunaan e-comic secara konsisten memberikan dampak positif terhadap pengembangan keterampilan berpikir kritis dan hasil belajar siswa, khususnya di jenjang sekolah dasar dan menengah. Media e-comic terbukti meningkatkan kemampuan analisis, evaluasi, serta kemampuan menyimpulkan informasi melalui konteks naratif yang menarik dan visual yang interaktif. Selain itu, rata-rata peningkatan hasil belajar siswa mencapai 15–30% setelah penggunaan e-comic dalam proses pembelajaran. Keberhasilan ini dijelaskan melalui teori pembelajaran multimedia Mayer, di mana kombinasi teks dan gambar memfasilitasi pemrosesan ganda (dual coding) sehingga memperkuat pemahaman konseptual dan retensi memori. Namun, sebagian besar penelitian masih terbatas pada desain kuasi-eksperimen dengan durasi intervensi yang singkat dan instrumen pengukuran berpikir kritis yang belum terstandarisasi. Dengan demikian, diperlukan penelitian lanjutan dengan desain eksperimen acak dan cakupan sampel yang lebih luas untuk menguji efektivitas jangka panjang. Secara keseluruhan, hasil SLR ini menegaskan bahwa e-comic BASAK merupakan inovasi pembelajaran digital yang efektif dalam mengembangkan kemampuan berpikir kritis dan hasil belajar siswa, serta relevan dengan tuntutan pembelajaran abad ke-21. Kata kunci: e-comic BASAK, berpikir kritis, hasil belajar, pembelajaran digital, SLR